Effect of different plant extracts on growth indices of tobacco caterpillar (Spodoptera litura) on soybean under laboratory conditions: Effect of different plant extracts on growth indices of tobacco caterpillar (Spodoptera litura) on soybean under laboratory conditions - NAVYA MATCHA; A K BHOWMICK (Journal of Oilseeds Research, 2020)
Spodoptera litura (F.) is a polyphagous insect among which soybean is one of its hosts. Six different botanicals i.e., three plant extracts (Datura leaf extract, Marigold leaf extract and Annona leaf extract) and three plant oils (Neem oil, Eucalyptus oil and Karanj oil) were used by preparing 5% aqueous solutions. Soybean leaves were treated with botanicals by leaf dip method and fed to prestarved second instar larvae and further studied their growth indices. The results indicated that Eucalyptus oil showed least larval index (0.45 in 3rd instar, 0.47 in 4th instar, 0.58 in 5th instar, 0.51 in 6th instar and 0.61 in pre-pupa), pupal index (0.44), adult index (only in case of males as 0.52) and lowest oviposition index (0.20). While, neem oil showed least adult index in females (0.82) and lowest total growth index (2.29).